The enduring promise of phosphodiesterase 5 inhibitors for colon cancer prevention - Browning, Darren D. (Translational Gastroenterology and Hepatology, 2019)
Cancers of the colon and rectum (CRC) are some of the most commonly diagnosed and are responsible for 9% of all cancer deaths due to the late stage of diagnosis where treatments are largely ineffective. Prevention of CRC is therefore very important for high-risk patients. The average lifetime risk of developing CRC varies widely between countries, but once diagnosed, the risk increases 3–5 folds for first-person relatives and for recurrence in the patient (1).